Moderating effects of organizational learning capability on the relationship between innovation, branding and SMEs performance in sports industry of Pakistan - Hafeez, Muhammad Haroon (2014)
Small and medium enterprises (SMEs) play a catalytic role in strengthening the economy of developing counties. The performance of SMEs depends on various factors. Among those factors include innovation and branding practices. This study aimed to investigate the nature of relationship that exists between Innovation, Branding and SMEs performance in sports industry of Pakistan. Furthermore, the study intended to examine the moderating effects of organizational learning capability on relationship between Innovation, Branding and SMEs performance. A structured questionnaire representing dimensions related to innovation, branding, organizational learning capability and SMEs Performance was designed. Survey method was used to conduct study on 352 SMEs in sports industry of Pakistan. Multiple Regression analysis was employed in order the study the nature and strength of relationship between Innovation and SMEs Performance, as well as between Branding and SMEs Performance. Results indicated that both Innovation and Branding have a significant positive effect on SMEs performance. Hierarchical Regression Analysis was utilized to see the moderating effects of Organizational Learning Capability on relationship between Innovation, Branding and SMEs performance. Findings revealed that Organizational learning Capability does not moderate the relationship between Innovation, Branding and SMEs performance. These results imply that SMEs must emphasize on bringing innovations and embracing branding practices if they desire to enhance their performance. The study also contributed to the theory as it extended Resource Based View, Dynamic Capabilities Perspective and the Theory of the growth of the firm by integrating three distinct literature streams pertaining to Innovation, Branding and Organizational Learning.